Performance of EuroSCORE II and logistic EuroSCORE in Bangladeshi population undergoing off-pump coronary artery bypass surgery: A prospective cohort study. (July 2019) - Ranjan, Redoy; Adhikary, Dipannita; Mandal, Sabita; Saha, Sanjoy Kumar; Hasan, Kamrul; Adhikary, Asit Baran
Introduction: European System for Cardiac Operative Risk Evaluation (EuroSCORE) was developed to identify patients who may have a greater postoperative risk for adverse effects following adult cardiac surgery. This study evaluated the discriminatory potential of using the EuroSCORE system in predicting the early, as well as late, postoperative outcomes following coronary artery bypass graft surgery in Bangladesh. Methods: A total of 865 patients who underwent isolated coronary artery bypass graft surgery were evaluated with the EuroSCORE risk scoring system. Moreover, we also compared the discriminatory potentials between the EuroSCORE II and the original logistic EuroSCORE. Results: Operative mortality was best predicted by EuroSCORE II (area under the curve (AUC) 0.863, Brier score 0.030) compared to the original logistic EuroSCORE (AUC 0.849, Brier score 0.033). However, the overall expected-to-observed mortality ratio for EuroSCORE II was 1.1, whereas the observed ratio for the original logistic EuroSCORE was 1.7. EuroSCORE II was predictive of an intensive care unit stay of five days or more (AUC 0.786), prolonged inotropes use (AUC 0.746), stroke (AUC 0.646), de novo dialysis (AUC 0.810), and low output syndrome (AUC 0.715). Moreover, a high EuroSCORE II quintile significantly predicted the risk for late mortality (p < 0.0001). Conclusions: EuroSCORE has an important role in predicting the early, as well as late, postoperative outcomes following coronary artery bypass surgery. However, the performance of EuroSCORE II is significantly better than the original logistic EuroSCORE in predicting postoperative morbidity and mortality after isolated coronary artery bypass graft surgery among Bangladeshi patients.